THE ADMINISTRATION OF CONTRACTUAL DELAY AND DISPUTE RESOLUTION IN THE UAE - Morris, Terence Anthony (2015)
This thesis examines the approach of the parties towards administering the conditions of contract with regards to contractual delay and ascertain as to why construction projects in the UAE are notoriously late in project delivery and why so many projects find themselves in dispute. Throughout the course of my studies the forms of contract available to the Employers and their consultants were studied and found to be quite extensive and the dispute mechanisms presented by them were found to be fair to both parties to the contract. What research establishing was that the most common forms of contract were the FIDIC 1987 and FIDIC 1999 “Red Book” contracts. Considering the dispute mechanisms within these contracts, why is it that the parties find themselves so often engaged in formal dispute and particularly arbitration. The research was conducted through an on-line survey of one hundred construction professionals for which there were seventy three respondents. The questions ranged from but were not limited to: 1. The causes of delay most commonly experienced, 2. The party most commonly found to be the cause of the delay, 3. The most common form of contract utilized in the UAE, 4. How the conditions of contract were applied, and 5. What were the contractual outcomes in the form of dispute resolution applied? The data provided supported my own experience whilst working on projects in the UAE for the last ten years that the choice of contract made was superficial, as the majority of contracts were bespoke and heavily weighted towards the Employer. Despite this what was evident was that no matter the form of contract, the Employer and his consultants constantly failed in the administration of the contracts leading to formal dispute. The UAE is developing its structure towards having a modern system of dispute resolution that would encourage in particular the likes of Mediation and International Arbitration. What is clearly displayed by the data received from this research is the Employers willingness to allow disputes to evolve and carry on for protracted periods of time with detriment to the project and the relationship of the parties. Would the industry and the parties to the contract be better advised or encouraged to administer the conditions of contract and address the disputes at the time of its occurrence as with the use of a Dispute Adjudication Board, or Mediation rather than the costly exercise of Arbitration?